(y/x-y  +  x/x+y):(1/x^2  +  1/y^2)-y^4/x^2-y^2 упростите

(y/x-y  +  x/x+y):(1/x^2  +  1/y^2)-y^4/x^2-y^2 упростите
Гость
Ответ(ы) на вопрос:
Гость
1) [latex] \frac{x}{x-y} + \frac{x}{x+y}= \frac{xy+ y^{2}+ x^{2} -xy }{ x^{2} - y^{2} }= \frac{ x^{2} + y^{2} }{ x^{2} - y^{2} } [/latex] 2) [latex] \frac{1}{ x^{2} }+ \frac{1}{ y^{2} } = \frac{ x^{2} + y^{2} }{ x^{2} y^{2} } [/latex] 3) [latex] \frac{ x^{2} + y^{2} }{ x^{2} - y^{2} } : \frac{ x^{2} + y^{2} }{ x^{2} y^{2} } = \frac{ x^{2} + y^{2} }{ x^{2} - y^{2} } * \frac{ x^{2} y^{2} }{ x^{2} + y^{2} } = \frac{ x^{2} y^{2} }{ x^{2} - y^{2} } [/latex] 4) [latex] \frac{ x^{2} y^{2} }{ x^{2} - y^{2} } - \frac{ y^{4} }{ x^{2} - y^{2} }= \frac{ x^{2} y^{2}- y^{4} }{ x^{2} - y^{2} } = \frac{ y^{2}( x^{2} - y^{2} ) }{ x^{2} - y^{2} }= y^{2} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы